A Research on the Crisis Spillover Effect of Food Safety Incidents on Competitive Firms: The Influence of Political Connections and Charitable Donations - Xiang, Rong; Wang, Mengqi; Lin, Li; Wu, Dongxia (Frontiers in Public Health, 2021)
Taking the perspective of corporate social responsibility and institutional theory, this research establishes an innovative relationship between variables such as charitable donation, political connection and crisis spillover effect of firms through quantitative analysis using the event study method, regression analysis and the Heckman two-stage model. Taking 8 food safety incidents from 2011 to 2016 as research samples, this paper studies the impact of food safety incidents on the market value of both firms under crisis and their competitive firms, as well as the influence of political connection and charitable donation. The conclusions are as follows: first, the occurrence of food safety incidents not only has a negative impact on the market value of the crisis firm, but also has a negative spillover effect on the competitive firm; second, charitable donations made by the competitive firm before the crisis demonstrates a positive competitive effect on the competitive firm, and the intensity of such charitable donations is positively correlated with this positive competitive effect; third, the political connection of the competitive firm has no significant impact on the crisis spillover effect. These findings provide enlightenment for the operation and management of firms in the food industry.